Biofertilizantes en el rendimiento de forraje de Pennisetum sp. “cuba 22” en forma aislada como en asociación con Canavalia ensiformis “canavalia” en Zungarococha, Perú – 2023 - Gomez Macahuachi, Nikolay Basteer (2025)
The association and complementary application of foliar biofertilizers in different forages is an alternative for livestock feeding in the humid tropics and the Faculty of Agronomy of the National University of the Peruvian Amazon proposes different alternatives such as the present work entitled BIOFERTILIZERS IN THE FORAGE YIELD OF Pennisetum sp. “CUBA 22” IN ISOLATION AND IN ASSOCIATION WITH Canavalia ensiformis “CANAVALIA” IN ZUNGAROCOCHA, PERU – 2023. The evaluation was carried out 60 days from the time of sowing with experimental units of 3 m x 1.2 m (3.6 m2) and an experimental area of 170 m2. Using a Complete Randomized Block Design (CBD), with a 2 x 2 factorial arrangement, the treatments under study were: T1 (humus leachate + Cuba 22), T2 (humus leachate + Cuba 22 associated with canavalia), T3 (biol + Cuba 22) and T4 (Biol + Cuba 22 associated with canavalia), the evaluation was 60 days after sowing, showing the following results: treatment T4 (Biol + Cuba 22 + canavalia association) with respect to plant height is 2.14 meters. With respect to green matter yield, it achieved 4.26 kg/m2, dry matter of 1.07 kg/m2, leaf weight of 1.925 kg/m2, stem weight of 2.34 kg/m2 and yield of 42,600 kilos per hectare.